Manual de prevenção e tratamento de lesões por fricção - Torres, Frank da Silva [UNIFESP] (2016)
Background: Skin tear is a superficial wound limited to the dermis, whose main characteristic is the presence of a skin flap. It has several contributing factors and little information is available on decision-making in routine practice for the management of preventive and therapeutic interventions. Objective: To develop a manual for the prevention and treatment of skin tears. Methods: A literature review on skin tears was conducted for the development of the manual. It was organized into seven chapters on skin tears with topics of interest to the professional. The manual was validated by health professionals specialized in skin tears. The Delphi technique was used as the validation method. Results: Seven experts with master's or doctoral degree validated the manual at two evaluation stages. The content validity index (CVI) was 6.7 for "Objectives", 10.55 for "Structure and Presentation", and 3.7 for "Relevance". The overall CVI was 0.95, confirming the validity of the manual. The manual has seven chapters, 27 pages, and 24 illustrations. Conclusion: A manual for the prevention and treatment of skin tears was developed and validated for use by health professionals.